2005
DOI: 10.1021/bm049254t
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer DNA/Poly(allylamine hydrochloride) Microcapsules:  Assembly and Mechanical Properties

Abstract: We report the preparation, characterization, and mechanical properties of DNA/poly(allylamine hydrochloride) (PAH) multilayer microcapsules. The DNA/PAH multilayers were first constructed on a planar support to examine their layer-by-layer buildup. Surface plasmon resonance spectroscopy (SPR) showed a nonlinear growth of the assembly upon each bilayer deposited independently on a concentration of salt. A weak increase in the film thickness with the DNA concentration was, however, detected. A post-treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 60 publications
10
74
0
Order By: Relevance
“…The best characterized pair of polyelectrolytes for layer by layer deposition is poly(allyl amine hydrochloride)/poly(sodium styrenesulfonate) (PAH/PSS) (for a review, see [891]). This pair has also been used for all AFM force experiments on PMCs except for [892], where also polyethyleneimine (PEI) and poly(diallyl-dimethyl-ammonium chloride) (PDADMAC) were used as polycations and [893], where DNA was used as polyanion. As template materials, melamine formaldehyde (MF), polylactic acid (PLA), weakly cross-linked polystyrene (PS), and MnCO 3 have been used.…”
Section: Mechanical Properties Of Microcapsulesmentioning
confidence: 99%
See 1 more Smart Citation
“…The best characterized pair of polyelectrolytes for layer by layer deposition is poly(allyl amine hydrochloride)/poly(sodium styrenesulfonate) (PAH/PSS) (for a review, see [891]). This pair has also been used for all AFM force experiments on PMCs except for [892], where also polyethyleneimine (PEI) and poly(diallyl-dimethyl-ammonium chloride) (PDADMAC) were used as polycations and [893], where DNA was used as polyanion. As template materials, melamine formaldehyde (MF), polylactic acid (PLA), weakly cross-linked polystyrene (PS), and MnCO 3 have been used.…”
Section: Mechanical Properties Of Microcapsulesmentioning
confidence: 99%
“…Future studies could include improvements of the mechanical models including finite permeability of the shells or widen the range of polyelectrolytes. An example for the latter case is the recent paper by Vinogradova et al [893] on PAH/DNA microcapsules. The inclusion of biomolecules as polyelectrolytes or polyamphylytes could also lead to biological applications that mimic biocompartments.…”
Section: Filled Polyelectrolyte Capsulesmentioning
confidence: 99%
“…[67] Vinogradova et al have also prepared different types of stimuli-sensitive LbL microcapsules with DNA/PAH. [115] Caruso's work on hollow DNA microcapsules comprising negatively charged homopolymeric nucleotides (polyA 20 G 20 / polyT 20 C 20 ) provided interesting results. [116] These microcapsules are likely to have diverse applications in delivery and sensing devices due to their switchable morphology and responsive behavior.…”
Section: Biological and Natural Materialsmentioning
confidence: 99%
“…[74] Vinogradova et al have measured the Young's modulus of DNA/PAH microcapsules by deformation experiments, and found the Young's modulus values to be in the 100 MPa range. [115] Kharlampieva and Sukhishvili have shown an interesting interplay between hydrogen-bonding and electrostatic interactions in hybrid polymer multilayers. [123] A recent study has shown that the microcapsule shell can be ultrasoft, with the apparent elastic modulus being less than 1 MPa.…”
Section: Micromechanical Propertiesmentioning
confidence: 99%
“…This technique is based on the sequential adsorption of oppositely charged polyelectrolytes onto the surface of charged colloidal particles which are used as templates (2,3). Not only have synthetic polymers (2,4,5) and biopolymers (6)(7)(8) served as layer constituents, but enzymes (9), nucleic acids (6,10), lipids (11) and nanoparticles (12,13) have also been incorporated in LbL shells (14). Furthermore, different types of templates have been considered, including biological cells (15), drug crystals (16,17), organic (18)(19)(20) and inorganic (21,22) colloidal particles.…”
Section: Introductionmentioning
confidence: 99%